(untitled) (Revista Contexto & Educação, 2026)
Evaluating dental training is essential. This study aimed to map and synthesize the literature on which items have been used to assess dentist training according to the National Curricular Guidelines (DCNs) in Brazil. A scoping review was conducted according to the Preferred Reporting Items for Systematic Review and Meta-Analyses for Scoping Reviews checklists and the Joanna Briggs Institute Manual, based on the following question: Which items have been used to assess dentist training according to the DCNs in Brazil? The mnemonics used were: Population (P) – dentist; Concept (C) – assessment of higher education; and Context (C) – DCNs. The search was conducted in August 2025 in the Central Cochrane Database, SciELO, MEDLINE via PubMed, Web of Science, Scopus, Virtual Health Library, Google Scholar, Embase, Brazilian Digital Library of Theses and Dissertations, CAPES Catalog of Theses and Dissertations, and ProQuest, using descriptors combined by Boolean operators. Brazilian quantitative research (2002-2025) in Portuguese, English, or Spanish was included, and postgraduate studies with professionals trained outside the educational environment, experience reports, opinion articles, and reviews were excluded. The selection, conducted by two reviewers with the support of a third, resulted in 16 papers out of 4,154, evaluated using the Critical Appraisal Skills Program checklist. The most addressed dimension was Graduate profile, with an emphasis on the Specific skills component, particularly items related to Pharmacology. Most articles and dissertations from the Southern region were cross-sectional in design, administering questionnaires to undergraduates. A scarcity of publications on the evaluation of dental education in Brazil was noted.